Pancreatitis aguda inducida por hipertrigliceridemia y tratamiento con plasmaféresis : reporte de un caso (2012)
Hypertriglyceridemia (HTG) is a potential cause of acute pancreatitis (AP), especially when its value is higher than 1.000 mg/dL. Different therapeutic measures have been proposed for patients with AP secondary to HTG, including the one that seems to be more effective: plasmapheresis. We report the case of a patient with severe HTG (triglycerides 6.480 mg/dL) that suffered from AP, and had favorable evolution with plasmapheresis.